Zoologi Literature Reading Interest Analysis on High Level Thinking of Ability Biology Education Students - Bunga Ihda Norra (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2021)
This study aimed to describe the relationship between reading interest in vertebrate zoology teaching materials with high order thinking skills. The method used is correlational research (descriptive). The population in this study were students of 2015 and 2016 Biology education at the Faculty of Science and Technology at UIN Walisongo Semarang with a sample of 113 students. Data of reading interest was captured by student answers through statements on questionnaires, while high order thinking skills are captured by description tests. Both of these data were analyzed by the Spearman correlation test, Regression and t-test. The results showed that there was a significant relationship between reading interest and high order thinking skills ability of students at α = 0.05 (sig. 0,000), but the relationship is in the low category (r = 0.326). And there are differences in reading interest and high order thinking skills ability between the 2015 and 2016 classes. Thus, reading interest needs to be increased because it has a relationship with students' high order thinking abilities.Penelitian ini bertujuan untuk mendeskripsikan hubungan antara minat baca bahan ajar zoologi vertebrata dengan kemampuan berpikir tingkat tinggi. Metode penelitian yang digunakan adalah penelitian korelasional. Populasi pada penelitian ini adalah mahasiswa pendidikan Biologi angkatan 2015 dan 2016 di Fakultas Sains dan Teknologi di UIN Walisongo Semarang, sampel penelitian sebanyak 113 mahasiswa. Data minat baca dijaring oleh jawaban mahasiswa melalui pernyataan pada angket, sedangkan keterampilan berpikir tingkat tinggi dijaring dengan tes uraian. Kedua data tersebut dianalisis dengan uji korelasi Spearman, Regresi dan t-test. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara minat baca dengan kemampuan berpikir tingkat tinggi mahasiswa pada α=0,05 (sig. 0,000), namun hubungan tersebut berada pada kategori rendah (r=0,326). Selain itu, terdapat perbedaan minat baca dan kemampun berpikir tingkat tinggi antara angkatan 2015 dan 2016. Dengan demikian, perlu ditingkatkannya minat baca karena memiliki hubungan dengan kemampuan berpikir tingkat tinggi mahasiswa.Kata kunci: kemampuan berpikir tingkat tinggi, minat membaca, zoologi vertebrata DOI: http://dx.doi.org/10.23960/jbt.v9i1.21728